2023
DOI: 10.1002/adfm.202215051
|View full text |Cite
|
Sign up to set email alerts
|

Spin Polarization of Chiral Amorphous Fe‐Ni Electrocatalysts Enabling Efficient Electrochemical Oxygen Evolution

Abstract: Chiral-induced spin selectivity is recently demonstrated in a range of spindependent optoelectronics and electrochemistry. Herein, a new type of amorphous chiral tartaric acid-FeNi coordination polymer fabricated by electrodeposition methods, achieving both high spin-polarization and high electrocatalytic activity for oxygen evolution, is reported. Circular dichroism shows signature optical activity from the coordination polymer. Conductive atomic force microscopy measurements demonstrate a high spin polarizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 66 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…It would be interesting and significant that different circularly polarized light can modulate the spin state of catalysts, thus leading to the selective catalytic production of different chiral molecules. Recent research has revealed that chiral-induced spin selectivity (CISS) can be observed in various spin-dependent optoelectronics and electrochemistry. CISS suggests that the molecular chirality and electron spin of chiral systems are highly correlated, meaning that electron spins become polarized as they pass through chiral systems. It has been proposed that the spin-polarized electrons generated by the CISS can interact with the catalyst surface, leading to an enhanced activity in the OER/ORR.…”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting and significant that different circularly polarized light can modulate the spin state of catalysts, thus leading to the selective catalytic production of different chiral molecules. Recent research has revealed that chiral-induced spin selectivity (CISS) can be observed in various spin-dependent optoelectronics and electrochemistry. CISS suggests that the molecular chirality and electron spin of chiral systems are highly correlated, meaning that electron spins become polarized as they pass through chiral systems. It has been proposed that the spin-polarized electrons generated by the CISS can interact with the catalyst surface, leading to an enhanced activity in the OER/ORR.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike organic molecules, chiral inorganic nanomaterials may exhibit better chiroptical activity due to high electrical polarization and magnetic susceptibility, , thus advancing multiple fields such as polarization-related imaging, biosensing, and chiral photonics. , Additionally, chiral inorganic materials with their inherent stability and conductivity hold great promise for catalysis. Recent studies have demonstrated that chiral materials can act as spin filters during electron transport, directing electrons toward favored polarization via chiral-induced spin selectivity. This provides a novel approach to improve the photo/electrocatalytic performance, beyond the conventional methods such as modulating the binding structure of catalysts or applying magnetic fields. Previous efforts to explore this concept often involved incorporating organic chiral components into inorganic materials such as coating or intercalating organic chiral molecules onto or into inorganic nanomaterials. , Electrodeposition has also been employed to fabricate chiral inorganic films. Despite the progress made, concerns regarding chiral instability and limited control over chiroptical activity have hindered exploration of the intricate relationship between the chiroptical effect and catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…12−16 Moreover, various intermediates like the formation of *O and *OOH have presented significant long-term challenges in devising efficient water splitting catalysts. 17 Consequently, there is an urgent need to design anode catalysts with exceptional OER performance.…”
mentioning
confidence: 99%
“…With the excessive utilization of fossil fuels and the escalating greenhouse effect, promoting energy transformation has emerged as a global objective. The volatility and inertness of renewable energy sources, such as wind and solar energy, present a formidable challenge to energy utilization. Electrochemical water splitting, as a technology for producing hydrogen which can be stored and utilized to maintain balance between energy supply and demand, is extensively studied. Among the various electrolytic water technologies, polymer electrolyte membrane water electrolyzes (PEMWEs) have received considerable attention due to the fast response to fluctuating electricity, higher current densities, and compact stack designs. However, the anodic oxygen evolution reaction (OER), as the key rate-limiting step of PEMWE, involves a complex four-electron transfer process and thus displays slow reaction kinetics and high overpotential. Moreover, various intermediates like the formation of *O and *OOH have presented significant long-term challenges in devising efficient water splitting catalysts . Consequently, there is an urgent need to design anode catalysts with exceptional OER performance.…”
mentioning
confidence: 99%